Rational Prepayment and the Valuation of Mortgage-Backed Securities - Stanton, Richard (Review of Financial Studies, 1995)
Journal Article Rational Prepayment and the Valuation of Mortgage-Backed Securities Get access Richard Stanton Richard Stanton University of California, Berkeley Address correspondence to Richard Stanton, Haas School of Business, University of California, Berkeley, 350 Barrows Hall, Berkeley, CA 94720. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 8, Issue 3, July 1995, Pages 677–708, https://doi.org/10.1093/rfs/8.3.677 Published: 28 May 2015